The Security Level Of Two Xored-based A5 Crypto System - Nur Hafiza Zakaria; Kamaruzzaman Seman; Ismail Abdullah (Institut Teknologi Bandung, 2024)
A5/1 is a stream cipher used to supply over the air communication privacy in the GSM cellular telephone standard. It was at first kept secret, but became open knowledge through leaks and reverse engineering. The purpose of this paper is to compare the security level of two (2) XORed-based A5 crypto systems. Five (5) statistical tests were used to test the strength of the algorithm. Both of the proposed modified XORed-based A5/1 algorithms successfully passed the five (5) statistical tests.